Constructability: The key to reducing investment risk - Chasey, Allan; Schexnayder, Ann (Acta Structilia, 2000)
The National Technology Roadmap for Semi-conductors indicates that the growth of the advanced technology factory cost is creating an exponential growth in factory investment risk. Management techniques are needed to help reduce that investment risk. Constructability implementation, if performed right, is a management concept that has been shown to reduce construction costs by 10 to 20 times its implementation cost. A corporate and project level constructability implementation program was developed by the Construction Industry Institute (CII) to help integrate construction knowledge with engineering, beginning at project inception. This article provides an historical base describing the development of constructability, constructability program criteria, and the constructability review process.